(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Pesisir Selatan Regency, West Sumatra, has great natural wealth and ecotourism potential. However, this region faces the challenges of high rates of stunting and extreme poverty due to limited access to health and nutrition services. Data from the Central Statistics Agency (BPS, 2023) shows a significant decrease in extreme poverty, but the prevalence of stunting has increased from 25.2% (2022) to 29.8% (2023). To address this, the Department of Economics, Faculty of Economics and Business, University of Andalas, conducted a community service activity to support one of the local business development programs through training and guidance in digital marketing. The activity was held in Nagari Bayang on October 27, 2024 (08:00 AM–16:00 PM WIB) with seven SMEs participating, using public participation and focused group discussion methods through guidance on utilizing e-commerce platforms as digital marketing tools to develop SMEs. The counseling session began with an explanation of the importance of digitalization in product sales and training on creating Shopee accounts for the SME participants, assisted by students. This was followed by a discussion session where participants could ask questions, share experiences, and identify issues and solutions in developing digital-based businesses. After the SMEs understood how to use Shopee accounts, practical transactions were conducted to provide hands-on experience in using Shopee accounts. All 7 SMEs now have Shopee accounts, have followers, and can conduct online transactions. It is hoped that this activity will increase income and support improved nutrition for the community in the area.